Sifat Fisik Air Minum Di Desa Sukasari, Pulosari, Pandeglang, Banten (Program Tahun 2022) - Edy Parwanto; David Tjahyadi; Sisca Sisca (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Aims of this Pengabdian Kepada Masyarakat (PKM) to determine the physical properties of drinking water in Sukasari Village, Pulosari, Pandeglang, Banten in 2022. Furthermore, the characteristics of the drinking water are informed to residents who consume it. Knowing to the physical properties of drinking water sourced from local springs in Sukasari Village, Pulosari, Pandegalang, Banten, the public can know and implemented it to the health of the drinking water they consume. The method used is to measure the physical properties of drinking water in the form of temperature, pH, total dissolved solid (TDS), smell and color. The result of this PKM are: temperature of drinking water ranges from 26.2 - 29.4 oC, pH ranges from 5.2-5.5, and the TDS is 11 ppm. In conclusion, the physical properties of drinking water (temperature, pH, TDS, smell, and color) in Sukasari Village, Pulosari, Pandeglang, Banten can still be consumed, provided that the pH of the drinking water is slightly acidic (not neutral). Based on the physical properties of drinking water which include temperature, pH, TDS, smell, and color has a positive significance to the health of the population who consume it. The positive implication of this PKM is to clarify the factors that can change the physical properties of drinking water from drinking water sources to people's homes. The existence of drinking water reservoirs has a positive impact on the physical properties of drinking water, especially on pH stability and TDS.